Becoming Self-Aware—How Do Self-Awareness and Transformative Learning Fit in the Sustainability Competency Discourse? - Jaakkola, Noora; Karvinen, Meeri; Hakio, Kirsi; Wolff, Lili-Ann; Mattelmäki, Tuuli; Friman, Mervi (Frontiers in Education, 2022)
An ever-growing number of scholars are developing and applying competency frameworks in the context of sustainability education. Despite the strong interest, most of the research has ignored the varying meanings of competency, which can be interpreted as a performed ability, but also as personality development. UNESCO (the United Nations Educational, Scientific and Cultural Organization) recently suggested self-awareness to be a central sustainability competency. However, the sustainability competency discourse is lacking a thorough analysis of how and if personality development related dispositions can be considered as competencies, how can they be taught in higher education, and how can the potentially transformative experiences resulting from such teaching be considered. In this article, we aim at a deeper understanding of the concept of self-awareness and its interpretations. We have reviewed the roots and analyzed the current interpretations of self-awareness in sustainability competency research and explored how the competency frameworks connect to transformative learning. In addition, we give tangible examples from art based and creative practices of design education, in which we have examined how self-awareness is defined and how it connects to transformative learning. The interpretations of self-awareness addressed two perspectives: awareness of oneself and awareness of one's relation to others and a wider society. Based on our research, becoming self-aware is a process that nourishes transformative learning. We additionally understand self-awareness as a process of internal growth instead of only a performable ability. This needs to be considered when developing the sustainability competency frameworks and their applications in education.